The Relationship between Real Earnings Management and Firm Performance: The Case of Energy Firms in Vietnam - Khuong, Nguyen Vinh; Ha, Nguyen Tran Thai; Thu, Phung Anh (International Journal of Energy Economics and Policy, 2019)
This investigation analyses the influence of real activities earnings management on firm performance of the energy listed firms on Vietnam’s stock market. Our data collection constitutes 29 energy companies on Vietnam stock markets (HNX and HOSE) in the period from 2010 to 2016. We used regression analysis in accordance with panel data, namely fixed effects model and random effects model. The results determine that real activity earnings management positively impacts on firm performance. This implies that increasing current sales activities will have a positive impact on current earnings. However, this may be pernicious to the company in the future. There is a positive association between firm size, cash from operating activities, growth opportunities and firm performance while firm leverage and tangible asset have a negative association. Research results are significant for regulators and investors in emerging markets. Keywords: real earnings management, firm performance, energy firms, Vietnam. JEL Classifications: M41; G32 DOI: https://doi.org/10.32479/ijeep.7469